1989
DOI: 10.1016/0014-5793(89)80265-0
|View full text |Cite
|
Sign up to set email alerts
|

Generation of O2 and tyrosine cation‐mediated chemiluminescence during the fertilization of sea urchin eggs

Abstract: Sea urchin eggs emit light in the visible region during their fertilization. Judging from the chemiluminescence spectra, one of the excited species generated is considered to have originated from a tyrosine cation radical-mediated reaction. Chemiluminescence probes such as luminol or a cypridina luciferin analog (2-methyl-6-[p-methoxyphenyl]-3,7-dihydroimidazo-[l,2-a]pyrazin-3-one) are useful for detecting the ovoperoxidase÷H202 reaction associated with membrane hardening and 02 generation, respectively, durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…[2][3][4][5] All the results are consistent with pathological or physiological significance of biophoton emission. Samples from human beings, including smoker's breath and serum, also exhibit ultraweak light emission.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…[2][3][4][5] All the results are consistent with pathological or physiological significance of biophoton emission. Samples from human beings, including smoker's breath and serum, also exhibit ultraweak light emission.…”
supporting
confidence: 74%
“…Image processing for elimination of background noise induced by high-energy particles was applied with threshold filtering. The average emission intensity in the total region of the tumor was evaluated after subtraction of U 5 To whom correspondence should be addressed. E-mail: noriaki-o@umin.ac.jp the background emission of the mouse determined at a circular region of 600-800 pixels between the blade bones, which exhibited good reproducibility with the lowest biophoton emission in the body of the mice.…”
Section: Methodsmentioning
confidence: 99%
“…Sea urchin eggs produce ROS after fertilization, 3) and NAD(P)H oxidase present in the egg cortex is thought to be the enzyme system responsible for ROS generation. 4) In sea urchin eggs, ROS generated by NAD(P)H oxidase is thought to act by hardening the fertilization membrane to protect fertilized eggs from additional sperm and pathogens.…”
Section: Notementioning
confidence: 99%
“…4) In sea urchin eggs, ROS generated by NAD(P)H oxidase is thought to act by hardening the fertilization membrane to protect fertilized eggs from additional sperm and pathogens. 3) As for ROS production during fish embryogenesis, the zebrafish embryo has been reported to produce ROS when stimulated with PMA.…”
Section: Notementioning
confidence: 99%
“…This change and other generation of forces and substances during cleavage would produce light emission. In the early development process, the chemiluminescence due to fertilization was studied in sea urchin egg and it was revealed that 0, and tyrosine cation, whose residues hardened the fertilization membrane surface, mediated the chemiluminescence (Takahashi et al, 1989). In the present study, the emission of light was detected from the surface of embryos of the frog, Rana japonica, during early cleavage by a photon counting and an "analog separation (integrated photons) method".…”
Section: Introductionmentioning
confidence: 99%